Community perceptions and acceptability of insecticide-treated screens for mosquito proofing of unimproved houses in Chalinze district, Tanzania: a mixed-methods study - Kihwele, Fadhila; Odufuwa, Olukayode G.; Muganga, Joseph B.; Mbuba, Emmanuel; Philipo, Rose; Moore, Jason; Skovmand, Ole; Bosselmann, Rune; Bradley, John; Moore, Sarah; Mboma, Zawadi Mageni (Frontiers in Malaria, 2025)
BackgroundUnimproved housing is a risk factor for malaria. Therefore, netting incorporated with deltamethrin and piperonyl butoxide, supplied as a roll to screen opened eaves, windows, and holes in the walls of unimproved houses, could offer protection by killing and/or reducing the entry of mosquitoes into a house. This study assessed the community perceptions and the acceptability of insecticide-treated screens (ITS), previously described as insecticide-treated eave nets (ITENs) and insecticide-treated window screens (ITWS).MethodologyA mixed-methods approach was implemented in three villages of the Chalinze District in Tanzania. This approach comprised in-depth interviews (IDIs) of the local carpenters who installed the ITS, focus group discussions (FGDs) with community members in both the ITS and control arms, and the administration of a structured questionnaire to members in the ITS arm. Data collection was conducted at 6 and 12 months post-installation. A thematic framework approach was used to identify and extract relevant themes from the qualitative data, including but not limited to community perceptions, acceptability, and adverse events, which were quantified using quantitative data. Furthermore, a separate structured questionnaire was administered during ITS installation to collect information on the time required for installation and the amount of netting used per house (214) in order to assess the cost implications of rolling out ITS in the community.ResultsThe ITS were perceived to reduce the entry of mosquitoes, other insects, and crawling animals such as snakes and lizards into houses. This intervention was accepted in the community, whereby the majority (95%) of participants expressed willingness to purchase the netting if sold at an affordable price of 1,000–6,000 Tanzanian shillings (USD ≤2.50) per square meter. The average time for ITS installation was 1 h per house, using an average of 29.5 running meters of fabric netting from rolls with a width of 1.5 m. The average material cost of the ITS was USD 1.25 per kilogram in transport. In this study, the average installation cost per house was USD 6.6 using standard Tanzanian salary rates, half the annual cost of insecticide-treated nets (ITNs) for a five-person household.ConclusionInsecticide-treated screening for unimproved houses is a promising, adaptable, and acceptable tool to supplement the existing vector control tools. The community perceived the use of ITS as a feasible intervention. This study highlights the importance of intensive community engagement during the development of a novel intervention to promptly address concerns and improve its acceptability.